Case Study: Materials Selection for Replacing A Fractured Pendulum Holder of Charpy Impact Testing Machine Hung-Ta 8041a Type Based on the Working Load - Winarto Winarto; Eddy Widiyono; Nur Husodo; Atria Pradityana; Subowo Subowo (IPTEK Journal of Proceedings Series, 2019)
The pendulum holder of our Charpy impact testing machine HUNG-TA 8041A type has fractured as a result of fatigue so that, it needs a replament of this pendulum holder. In this case, we tried to select the appropriate material in order to avoid buying the new impact testing machine by repairing the fractured pendulum holder. To determine the new material, some tests have been carried out comprise of material tests using SEM-EDS, and also load analysis that works to the holder according to machine design theory, and next step is doing a verification using Ansys software and the result will be used as a base in choosing the material. Based on the material test that has been held, it is known that pendulum holder material is high carbon steel with carbon content is about 0.6%, and from the machine design analysis we found that the working load to the pendulum holder is 0.349 MPa, and finally from analysis using Ansys software it was found that the pendulum working load is 0.48 MPa, there is a different result as high as 37%. From those series of tests and analysis, the material selected to replace the broken holder is AISI 1060 steel